ARM7 Processor Simulator with Graphical User Interface - Khaw, Boon Chai; Zabidi, Muhammad Mun'im Ahmad (MiCE Dept, Universiti Teknologi Malaysia, 2007)
The paper describes an ARM7 processor simulator with graphical user interface (GUI) which is easy and suitable for the beginner. This software is written in Java language and the graphic user interface is written using Eclipse Standard Widget Toolkit (SWT). GNU toolchain is using as the compiler and assembler for this simulator to produce binary machine code for ARM. The simulator decodes the 32-bit ARM machine instructions and simulate the execution of every instruction.